EFFECTS OF AQUEOUS EXTRACTS OF ONION (Allium cepa) AND GARLIC (Allium sativum) ON ARSENIC-INDUCED TOXICITY IN RATS (2014)
Human exposure to arsenic toxicity poses a health problem. Allium cepa (AC) and Allium sativum (AS) have the potential to ameliorate the effects of arsenic toxicity and are widely used as condiments in Nigeria. A proper understanding of these possible ameliorating effects of AC and AS in reducing arsenic toxicity is important. This study was designed to assess the effects of AC and AS on arsenic-induced toxicity in rats. Seven weeks old male Wistar strain albino rats (Rattus novergicus) were acclimatized for 3 weeks. Lyophilized aqueous extracts of AC and AS were separately reconstituted in distilled water to give a concentration of 3 mg/L. Thereafter, the rats were randomly distributed into seven groups with five (5) rats in each group. Each group was given different treatments with dose equivalent of distilled water as follows: A (3 mg/L distilled water only, control), B (3 mg/L As2O3 only), C (3 mg/L AC extract only), D (3 mg/L AS extract only), E (3 mg/L each of AC and As2O3), F (3 mg/L each of AS and As2O3) and G (3 mg/L each of AC and AS extracts). Treatments were administered by gavage while maintaining the rats on commercial rat pellets and water ad libitum for 20 days. In addition to the baseline body weight, weights of rats, feed and water intake were recorded daily throughout the experiment. On day 20, the rats were sacrificed after which blood, liver, kidney, brain, testes, and spleen were removed for biochemical, haematological and histopathological examinations. Data were analysed using descriptive statistics, paired t-test and ANOVA at 5% level of significance. Weight change for groups A to G was: 21.7±9.8 g, 7.6±12.1 g, 0.9±4.1 g, 8.0±12.0 g, 3.6±2.2 g, 2.2±1.0 g and 34.2±1.6 g respectively. The feed intake per day for group E (62.2+11.8 g) was the highest and significantly higher when compared with 61.8+18.4 g for group B. However, group C (53.8±11.8 g), D (56.7±24.2 g) were significantly lower when compared with 72.3+14.7 g of the feed intake for control. Packed cell volume (47.3+3.8%) was highest in F and significantly higher in comparison with 45.0+3.6% for group B. White blood cell count was highest in E (10567cell/mm3) and significantly higher when compared with 7500 cell/mm3 for control. Total protein (8.2+0.2 g/dl) for group F was higher than 7.8+0.7 g/dl for the control but not significantly different. Albumin production was significantly lower in G (4.1+0.1 g/dl) than the control (4.6+0.1 dl). Blood urea nitrogen production was significantly lower in group F (14.0+1.0 dl) than the control (15.3+0.6g/dl). Group B showed nasal discharge, fur removal, ocular lesion, cytoplasmic degeneration around renal tubules of the kidney, tissue necrosis of the liver, nuclear pleomorphism of the brain, and aggregation of inflammatory cells of the spleen than A,C,D and G. However, groups E and F showed none of these effects. Based on the detoxifying effects of aqueous extracts of Allium cepa and Allium sativum on arsenic-induced toxicity in rats, their use as condiments among humans should be encouraged and possibly promoted.